Aligning the Ship Engine Cadets’ Skills to the 21st Century - Tabora, Brando T (Future Science / FSH-PH Publications, 2023)
The Philippines is one of the single largest nationality groups in the maritime and shipping sectors; as a result, the nation's efforts to modernize the skills of the engine cadets are significant. This study aimed to assess the engine cadets' skill level in relation to the requisite 21st-century skills while they were receiving shipboard training at TORM Shipping Philippines Inc. It used a sequential explanatory mixed-methods design. The paper used mean, standard deviation, and Mann-Whitney for comparing differences between two independent groups for the statistical treatment analyses of the quantitative data. Thematic analysis of the descriptive data provided by the interviewees involved coding and identifying common themes, patterns, and responses. The findings revealed that the engine cadets were competent in three (3) areas but needed to be more competent in the remaining area (inventive thinking). This signified that the engine cadets need supplemental training in the areas where they are less apt to improve their skills in all variables, especially 21st-century skills. The management of maritime schools and policymakers must address the common factors that prevent engine cadets from acquiring 21st-century skills, according to the study.